Engaging Human Sexuality: Creating Safe Spaces for LGBTIQ+ and Straight Believers in South Africa - Palm, Selina; Gaum, Laurie (Theologia in Loco, 2021)
The development of experiential human sexuality workshops within faith communities in South Africa (SA) is showcased. The findings from a 2019 empirical study with local church congregations around LGBTIQ+ belonging are used as starting point. The intervention brings together people of diverse sexualities and genders from various Christian faith contexts. Methodologies from a longstanding programme developed in the USA are adapted, that was shaped by learnings from the SA Truth and Reconciliation Commission. This is reworked into a continuum approach to sexuality and gender, developing new tools, and using the lens of intersectionality within the SA context. The article explores the potential and pitfalls of using the workshop piloted twice in 2020, more widely in faith settings to create spaces for safe encounter between straight and LGBTIQ+ people engaging on human sexuality, building solidarity and strengthening ally-ship. It concludes to show how an important gap within both LGBTIQ+ activism and theology is met.